The influence of bid premium on shareholder around M&A announcements: An empirical analysis - Tiller, Luke (2009)
Within the widely covered topic of mergers and acquisitions two of the most widely addressed subjects are shareholder wealth creation and premiums offered to target firms. However little work has combined both of these aspects in much detail, which has been noted (Haleblian et al., 2009). Yet in spite of the limited work in this area, many assume that higher premiums result in wealth creation for target firms at the expense of acquirers. This sweeping generalisation is challenged by the research presented here.